Patterns of Religious Practice Among Secondary School Moslem Students in Salatiga, Indonesia: an Analysis of the Religious Index in the Context of School - Achmad, Syaefudin; Maimun, Achmad (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2026)
Religiosity is an important aspect of human life, both for individuals and society, including in the context of education. This study aims to examine the patterns of religiosity among high school students in Salatiga City using a religious index analysis within the context of school education. The main focus of this research is to understand students’ religious understanding and their practice of worship in Salatiga. This study employs a mixed-method approach, combining quantitative (survey) and qualitative (case study) methods. Data were collected through questionnaires, interviews, observations, and documentation. The research was conducted at State Senior High School 1 and Muhammadiyah (Plus) Senior High School in Salatiga, located in the city of Salatiga. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed through data condensation, coding, data display, and conclusion drawing. The results indicate that the students' religiosity index shows significant variation, reflecting diverse levels of religious understanding and worship practices among students. This study provides insight into how school education contributes to shaping students' religiosity patterns. Theoretically, this research contributes to enriching the body of knowledge on religious education in schools.